Labour market impact of large scale internal migration on Chinese urban 'native' workers - Xin Meng; Dandan Zhang (Institute for the Study of Labor (IZA), 2010)
Hundreds of millions of rural migrants have moved into Chinese cities since the early 1990s contributing greatly to economic growth, yet, they are often blamed for reducing urban 'native' workers' employment opportunities, suppressing their wages and increasing pressure on infrastructure and other public facilities. This paper examines the causal relationship between rural-urban migration and urban native workers' labour market outcomes in Chinese cities. After controlling for the endogeneity problem our results show that rural migrants in urban China have modest positive or zero effects on the average employment and insignificant impact on earnings of urban workers. When examine the impact on unskilled labours we once again find it to be positive and insignificant. We conjecture that the reason for the lack of adverse effects is due partially to the labour market segregation between the migrants and urban natives, and partially due to the complementarities between the two groups of workers. Further investigation reveals that the increase in migrant inflow is related to the demand expansion and that if the economic growth continues, elimination of labour market segregation may not necessarily lead to an adverse impact of migration on urban native labour market outcomes.
Keywords: J80; J45; 330; migration; native labour market outcomes; China